2005
DOI: 10.1016/j.aap.2004.04.006
|View full text |Cite
|
Sign up to set email alerts
|

Traffic fatalities and economic growth

Abstract: This dissertation adds to the current understanding of the socioeconomic determinants of traffic fatality rates by examining the variation in road deaths across countries and over time. Chapter two investigates the relationship between road safety and economic development within an Environmental Kuznets Curve framework. Reduced-form models of fatality risk as a function of per capita income are estimated using panel data for over 80 countries. The results confirm an inverted U-shaped relationship with income, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

9
126
1
1

Year Published

2005
2005
2019
2019

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 385 publications
(137 citation statements)
references
References 40 publications
9
126
1
1
Order By: Relevance
“…Many cross-sectional and secular analyses have shown that an inverted U captures the statistical relationship between changes in injury mortality and changes in per capita gross domestic product (GDP). [14][15][16][17][18][19] In other words, injury mortality initially increases as GDP per capita grows, but once the GDP exceeds a certain threshold, injury mortality falls with further economic growth. 14,16 However, the per capita GDP marking the turning points in injury mortality varies considerably across countries, even for a given injury category -from about 3000 to 15 000 United States dollars (US$).…”
Section: Underlying Causes and Policy Implicationsmentioning
confidence: 99%
See 1 more Smart Citation
“…Many cross-sectional and secular analyses have shown that an inverted U captures the statistical relationship between changes in injury mortality and changes in per capita gross domestic product (GDP). [14][15][16][17][18][19] In other words, injury mortality initially increases as GDP per capita grows, but once the GDP exceeds a certain threshold, injury mortality falls with further economic growth. 14,16 However, the per capita GDP marking the turning points in injury mortality varies considerably across countries, even for a given injury category -from about 3000 to 15 000 United States dollars (US$).…”
Section: Underlying Causes and Policy Implicationsmentioning
confidence: 99%
“…14,16 However, the per capita GDP marking the turning points in injury mortality varies considerably across countries, even for a given injury category -from about 3000 to 15 000 United States dollars (US$). [14][15][16][17][18][19] These turning points reflect the adaptation of the national health-care system and of industrial, collective and personal countermeasures to lower injury risks, such as improved ambulance services, better occupational safety and helmet and seat belt use. Because injury mortality initially correlates with per capita GDP, [14][15][16][17][18][19] it is not surprising that China's urban prosperity over the past two decades (Table 2) has been accompanied by an increase in mortality from injury.…”
Section: Underlying Causes and Policy Implicationsmentioning
confidence: 99%
“…The number of vehicles per population Africa is still low in developing countries but still it has high RTAs [11]. It has been observed that with development the road traffic mortality will decline especially when both road conditions and health facilities to handle causalities will improve [5]. Since in Sub-Saharan Africa the stage of development is still far to be reached therefore there is a need to intervene the problem.…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, it is necessary to study the relationship between accident and economy growth. Kopits and Cropper [5], and Yannis [6] studied the relationship between traffic fatalities and economic growth. Carrion-i-Silvestre et al [7] analyzed the stationary of the real per capita health care expenditure (HCE) and real per capita GDP.…”
Section: Introductionmentioning
confidence: 99%